2014
DOI: 10.1021/jf502508y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolite Profiling ofSolanum tuberosumagainst Six WildSolanumSpecies with Colorado Potato Beetle Resistance

Abstract: The Colorado potato beetle Leptinotarsa decemlineata (Say) (CPB) is a coleopteran herbivore that feeds on the foliage on Solanum species, in particular, potato. Six resistant wild Solanum species were identified, and two of these species had low levels of glycoalkaloids. Comparative analysis of the untargeted metabolite profiles of the foliage using UPLC-qTOF-MS was done to find metabolites shared between the wild species but not with Solanum tuberosum (L.) to identify resistance-related metabolites. It was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
(109 reference statements)
3
26
0
1
Order By: Relevance
“…Foliar leptine glycoalkaloids are associated with poor larval development and high larval mortality. 10,17,34 These observations were also confirmed by our results. CPB larvae fed on S. chacoense HL leaves, which are known to produce the largest amount of leptine glycoalkaloids, developed slowly, and none reached the adult stage.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Foliar leptine glycoalkaloids are associated with poor larval development and high larval mortality. 10,17,34 These observations were also confirmed by our results. CPB larvae fed on S. chacoense HL leaves, which are known to produce the largest amount of leptine glycoalkaloids, developed slowly, and none reached the adult stage.…”
Section: Resultssupporting
confidence: 88%
“…15,16 In experiments conducted by Lorenzen et al, 10 CPB larvae fed with S. chacoense leaves developed more slowly than those fed cultivated potato leaves. Similar results were obtained by Tai et al, 17 who found that the foliar leptine glycoalkaloids are associated with a decrease in adult beetle feeding and an increase in larvae mortality.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, metabolic markers started to draw attention due to their close relationship with yield phenotypes (Fernie and Schauer, 2009;Redestig et al, 2011;Riedelsheimer et al, 2012aRiedelsheimer et al, , 2012bWitt et al, 2012;Degenkolbe et al, 2013). The accumulation of some metabolites has been reported to be directly related to the performance of potato (Solanum tuberosum) cultivars in beetle resistance in the field (Tai et al, 2014). Additionally, identical genomic regions were mapped as both agronomic and metabolic quantitative trait loci in field-grown maize and wheat (Triticum aestivum), indicating the utility of metabolic traits for breeding selection (Riedelsheimer et al, 2012b;Hill et al, 2015).…”
mentioning
confidence: 99%
“…A atividade antifúngica já foi descrita para α-solamargina, a qual inibiu o desenvolvimento micelial dos fungos P. medicaginis e R. solani WEISSENBERG, 1994). A bioatividade da leptinina I está relacionada com a inibição da herbívoria causada pelo besouro-da-batata (Leptinotarsa decemlineata) o qual é responsável por perdas entre 30-50% em plantações de batata (SHAKYA;NAVARRE, 2008;TAI et al, 2014). O que demonstra que os compostos α-solamargina, β-solamarina e leptinina I, "supostamente" avaliados neste trabalho, apresentam as mais diversas bioatividades.…”
Section: Abstract: Solanum Americanum; Moniliophthora Perniciosa; Inhunclassified